2020
DOI: 10.1038/s41598-020-76303-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of the decision tree method to lithology identification of volcanic rocks-taking the Mesozoic in the Laizhouwan Sag as an example

Abstract: The decision tree method can be used to identify complex volcanic rock lithology by dividing lithology sample data layer by layer and establishing a tree structure classification model. Mesozoic volcanic strata are widely developed in the Bohai Bay Basin, the rock types are complex and diverse, and the logging response is irregular. Taking the D oilfield of the Laizhouwan Sag in the Bohai Bay Basin as an example, this study selects volcanic rocks with good development scales and single-layer thicknesses of mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Based on the analysis of drilling data and seismic data, the Mesozoic, the target interval of this study, is revealed by drilling of D-4, D-6, D-7, D-9, and D-10 within the scope of the oilfield (Figure 2C). However, the drilling did not drill through the formation, and the thickness of the revealed formation is 11.8-215.0 m. The lithology of the study area mainly includes pyroclastic rock, lava and sedimentary pyroclastic rock (Duan et al, 2020b). This area belongs to low exploration area and has great exploration potential.…”
Section: Geological Backgroundmentioning
confidence: 98%
“…Based on the analysis of drilling data and seismic data, the Mesozoic, the target interval of this study, is revealed by drilling of D-4, D-6, D-7, D-9, and D-10 within the scope of the oilfield (Figure 2C). However, the drilling did not drill through the formation, and the thickness of the revealed formation is 11.8-215.0 m. The lithology of the study area mainly includes pyroclastic rock, lava and sedimentary pyroclastic rock (Duan et al, 2020b). This area belongs to low exploration area and has great exploration potential.…”
Section: Geological Backgroundmentioning
confidence: 98%